Assessing Cybersecurity service quality in corporate environments - Guerreiro, Rui Norberto Barcoso (2018)
This study assess the quality of Cybersecurity as a service provided by IT department in corporate network and provides analysis about the service quality impact on the user, seen as a consumer of the service, and on the organization as well. In order to evaluate the quality of this service, multi-item instrument “SERVQUAL” was used for measuring consumer perceptions of service quality. To provide insights about Cybersecurity service quality impact, DeLone and McLean information systems success model was used. To test this approach, data was collected from over one hundred users from different industries and partial least square (PLS) was used to estimate the research model. This study found that SERVQUAL is adequate to assess Cybersecurity service quality and also found that Cybersecurity service quality positively influences the Cybersecurity use and individual impact in Cybersecurity.